Palace ware across the Neo-Assyrian imperial landscape : social value and semiotic meaning - Hunt, Alice M. W. (Culture and History of the Ancient Near East, 2015)
In Palace Ware Across the Neo-Assyrian Imperial Landscape , Alice Hunt investigates the social and symbolic meaning of Palace Ware by its cultural audience in the Neo-Assyrian central and annexed provinces, and the unincorporated territories, including buffer zones and vassal states. Traditionally, Palace Ware has been equated with imperial identity. By understanding these vessels as a vehicle through which interregional and intercultural relationships were negotiated and maintained she reveals their complexity gaining a more nuanced view of imperial dynamics. Palace Ware Across the Neo-Assyrian Imperial Landscape is the first work of its kind; providing in-depth analysis of the formal and fabric characteristic, production technology, and raw material provenance of Palace Ware, and locating these data within the larger narratives of power, presentation, symbol and meaning that shaped the Neo-Assyrian imperial landscape.